Multiionic and Permittivity-Related Effects on the Diffuse Electric Double Layer Structure at Solid-Electrolyte Solution Interfaces. (30th September 2018) - López-García, J. J.; Horno, J.; Grosse, C.
Abstract : The structure and differential capacitance of the diffuse part of the electric double layer at solid-electrolyte solution interfaces are examined using a theoretical model that takes into account the finite ion size by modeling the solution as a suspension of polarizable insulating spheres in water. This formalism is applied to binary and mixed electrolyte solutions using the "Boublik–Mansoori–Carnahan–Starling–Leland" (BMCSL) theory for the steric interactions among ions. It is shown that the ionic size differences have a strong bearing on the diffuse part of the electric double layer structure, as well as on the differential capacitance dependence on the surface potential for mixed electrolytes.